Diabetes mellitus is associated with increased acute kidney injury and 1‐year mortality after transcatheter aortic valve replacement: A meta‐analysis. Issue 9 (16th May 2017) - Mina, George S.; Gill, Priyanka; Soliman, Demiana; Reddy, Pratap; Dominic, Paari
Abstract : Background: Diabetes mellitus (DM) is associated with adverse outcomes after surgical aortic valve replacement. However, there are conflicting data on the impact of DM on outcomes of transcatheter aortic valve replacement (TAVR). Hypothesis: DM is associated with poor outcomes after different cardiac procedures. Therefore, DM can also be associated with poor outcomes after TAVR. Methods: We searched PubMed and Cochrane Central Register of Controlled Trials for studies that evaluated outcomes after TAVR and stratified at least 1 of the studied endpoints by DM status. The primary endpoint was all‐cause mortality at 1 year. Secondary endpoints were early (up to 30 days) mortality, acute kidney injury (AKI), cerebrovascular accident (CVA), major bleeding, and major vascular complications. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using random effects models. Results: We included 64 studies with a total of 38 686 patients. DM was associated with significantly higher 1‐year mortality (OR: 1.14, 95% CI: 1.04‐1.26, P = 0.008) and periprocedural AKI (OR: 1.28, 95% CI: 1.08‐1.52, P = 0.004). On the other hand, there were no significant differences between diabetics and nondiabetics in early mortality, CVAs, major bleeding, or major vascular complications. Conclusions: DM is associated with increased 1‐year mortality and periprocedural AKI in patients undergoing TAVR. The results of this study suggest that DM is a predictor of adverse outcomes in patients undergoing TAVR.